Improving the ability to understand the concept of building space through PMRI-based with the help of smart classroom applications for students of primary school - Nur Cahaya Wigati; Pinta Deniyanti Sampoerno; Meiliasari Meiliasari; Jaka Wijaya Kusuma (SAINTIS Publishing, 2022)
The quality of education must be improved in order to create quality education. The Covid-19 virus that has infected most Indonesians since early March 2020 has impacted all areas of community movement. Restrictions on personal activities until the Implementation of Community Activity Restrictions (PPKM) began to be enforced. Physical distancing is one of the efforts made to limit community interaction. The government also decided to disburse students and shift schools' teaching and learning process to at home. Distance learning or online learning requires all school residents to work more actively in teaching and learning activities. The ability to understand concepts is one of the skills that are expected to be achieved in mathematics subjects. This study aims to determine the application of learning with the PMRI Approach assisted by the Smart Classroom application in improving the ability to understand the concept of building a classroom for grade V students of SDN Jakamulya III Bekasi City. This research was conducted quantitatively with 6 subjects as the object of study. The results of the study show that there is an increase in mathematics learning with the PMRI approach with the help of the Smart Classroom application. The results showed that the PMRI approach assisted by the Smart Classroom application for mathematics subjects in grade V elementary schools could help students understand the concept of building spaces. This is shown by the increase in positive responses from the start of cycles I, II, and III in scoring and interviews. Students are happy and facilitate learning through the Smart Classroom app. Moreover, there are online and offline learning systems and hybrid learning.